Effect of Variation of Mixture (Wood Gelam+Rice Husk) on Bio-Pellet on the Value of Temperature, Rate and Pressure of Combustion - Subagyo, Rachmat; Nugraha, Andy; Isworo, Hajar; Pratama, Trendy; Rusdi, M. Zainul (Fakultas Teknik Universitas Brawijaya, 2022)
The increasing demand for energy causes the depletion of fuel fossil. To overcome this, it is necessary to utilize biomass and biomass waste. The purpose of this study was to simulate the effect of bio-pellet density on temperature, rate and pressure of combustion made from a mixture of gelam wood and rice husk. The method uses ANSYS simulation with literature review. The results showed that the increasing composition of rice husks had an effect on the decreasing combustion rate, this was due to the calorific value of the pellets making up the material. Where the lower calorific value of rice husk has an effect on the rate of combustion. Pellets that have a large density affect the rate of combustion so that it extends the burning time. The density of pellets is influenced by the pressure of pellet molding, the greater the pressure makes the fuel denser and has a large density. The highest combustion air pressure occurs at 100% gelam composition and the lowest at 100% husk composition. This shows that the addition of rice husk composition reduces the combustion pressure and vice versa applies to the addition of gelam composition.